2020
DOI: 10.3390/jcm9051523
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Gestational Diabetes in Triplet Pregnancies: A Retrospective Cohort Study and Meta-Analysis

Abstract: Background: Over the last decades, there has been a substantial increase in the incidence of higher-order multiple gestations. Twin pregnancies are associated with an increased risk of gestational diabetes mellitus (GDM). The literature on GDM rates in triplet pregnancies is scarce. Methods: A retrospective cohort study was performed to assess the prevalence of GDM in women with a triplet pregnancy. GDM was defined through an abnormal oral glucose tolerance test (OGTT). A meta-analysis of GDM prevalence was al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 67 publications
0
7
0
1
Order By: Relevance
“…We use GPower 3.1.9.760 with 0.90 power and significance at two-sided α of 0.05 to estimate the smallest difference in maternal or neonatal complication rate between GDM with optimal glycaemic control and suboptimal control to be at 15%, the required sample size is 312 (104 cases and 208 control). For another estimation, the required sample size to estimate 10% (as the lowest possible proportion among all the risk factors) either the history of PCOS with the reported prevalence rate 12.6%30 or multiple pregnancies with reported incidence of 12%–30% among GDM women32 33 with the power 0.90 and α 0.05 at two tails is 263. Taking into consideration about 10% of incomplete or missing data in the home-based records, the sample size needed is 292 (263/0.90) cases and 584 (526/0.90) control at the ratio of 1:2.…”
Section: Methods and Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…We use GPower 3.1.9.760 with 0.90 power and significance at two-sided α of 0.05 to estimate the smallest difference in maternal or neonatal complication rate between GDM with optimal glycaemic control and suboptimal control to be at 15%, the required sample size is 312 (104 cases and 208 control). For another estimation, the required sample size to estimate 10% (as the lowest possible proportion among all the risk factors) either the history of PCOS with the reported prevalence rate 12.6%30 or multiple pregnancies with reported incidence of 12%–30% among GDM women32 33 with the power 0.90 and α 0.05 at two tails is 263. Taking into consideration about 10% of incomplete or missing data in the home-based records, the sample size needed is 292 (263/0.90) cases and 584 (526/0.90) control at the ratio of 1:2.…”
Section: Methods and Analysismentioning
confidence: 99%
“…Multiple pregnancies is associated with higher risk for GDM due to a higher weight gain rather than the number of fetus 31. The rate of multiple pregnancy deliveries among GDM women in Malaysia range approximately from 12% to 30% 32 33. Many GDM studies have excluded multiple pregnancies in their eligibility criteria, so the risk of multiple pregnancies on GDM is not clear.…”
Section: Introductionmentioning
confidence: 99%
“…Other group of researchers from Austria also analyzed the GDM prevalence in triplet pregnancies. The rate was absolutely higher (31.7%) than in singleton pregnancies [ 138 ].…”
Section: Europementioning
confidence: 99%
“…Obstetricians should choose appropriate instruments and be familiar with the procedure to reduce the operating time. It was reported that P r e p r i n t multiple pregnancy is a risk factor for gestational diabetes mellitus and hypertension [1,11,12]. A meta-analysis [11] showed that 7.3-12.4% of pregnant women with triplets had gestational diabetes mellitus.…”
Section: Discussionmentioning
confidence: 99%